دراسة سببية لنقص الصفيحات الدموية خبرة مشفى الأسد الجامعي بين عامي 2002 – 2003 - جرجس, ميخائيل; دبرها, نافع; علي, لؤي نعيم (Latakia University Journal -Medical Sciences Series, 2019)
ضمت دراستنا حالات نقص الصفيحات الدموية التي دخلت مشفى الأسد الجامعي باللاذقية " قسم الأمراض الباطنة " خلال العام 2003. شملت الدراسة /100/ حالة نقص صفيحات دموية " عدد الصفحات أقل من 100 ألف صفحة/ملم3 " وكانت الغاية هي معرفة أهم الأسباب الشائعة في بلادنا التي تؤدي إلى نقص الصفيحات الدموية وتصنيفها حسب آلية النقص محيطية أو مركزية وتوزع هذا النقص حسب العمر والجنس وأهم المظاهر النزفية المترافقة مع هذا النقص وترافق نقص الصفيحات مع عناصر الدم الأخرى ، وأهمية تحديد حجم الصفيحات الوسطي MPV في معرفة السبب هل هو مركزي أم محيطي. لقد تم التوصل إلى التشخيص عبر وسائل استقصائية عديدة منها الاستجواب والفحص السريري والفحوص المخبرية الدموية والكيمائية وفحوصات أخرى حسب التوجه السريري، بالإضافة إلى بزل النقي وخزعة النقي والفحوص الشعاعية حيث تم التوصل إلى عدة نتائج أهمها: كانت نسبة الإصابة عند الذكور أعلى بقليل من الإناث. إن أصحاب الأعمار المتقدمة > 50 سنة هم المعرضون لنقص الصفيحات الدموية أكثر من غيرهم والسبب غالباً أمراض الدم الخبيثة الدموية أما الشباب وخاصة الإناث فالسبب غالباً ITP "فرفرية نقص الصفيحات المناعية الذاتية". بالنسبة للآلية المرضية كان هناك رحجان بسيط للسبب المركزي. أهم الأسباب المركزية لنقص الصفيحات الدموية كانت أمراض الدم الخبيثة أما بالنسبة للسبب المحيطي فكان ITP. كانت معظم حالات نقص الصفيحات مشاركة لنقص عناصر الدم الأخرى. ترافق النزف مع الحالات التي كان فيها عدد الصفيحات أقل من (50) ألف صفحة/ ملم3. كانت أهم المظاهر النزفية هي الفرفريات ثم الكدمات. يمكن لتحديد حجم الصفيحات الوسطى MPV أن يكون مفيداً في تحديد سبب نقص الصفيحات سواء كان ناجماً عن نقص الإنتاج "MPV منخفضة" أو زيادة التحطم المحيطي "MPV طبيعي أو زائدة". Our study included cases of thrombo cytopenia which were admitted to Al- Assad University Hospital "Internal Medicine Department" during 2003. The study included "100" cases of thrombocyropenia " less than 100000 platelets/mm3 ". The goal of the study was to know the most common causes in our country that lead to thrombocytopenia, and its classification according to the mechanism (central or peripheral) and distribution of these causes according to age and sex, and the most important bleeding manifestation associated with them, and the importance of determination of mean platelet volume "MPV" determining if the cause is central or peripheral. The diagnosis has been done by several investigations such as History, clinical examination, hematologinal and chemical laboratory tests, and others tests according to clinical doubt. And bone narrow, bone biopsy. Xray exam too. Finally the most important results were: The prevelance of incidence in male was higher than females. People in their 50s are more liable to thrombocytopenia than young people espically females, the reason is usually ITP. According to the mechanism of pathogenic, there was little dominance of central causes. Most important causes of thrombocytopenia were malignant hemopathies, and for the peripheral causes were ITP. The most cases of thrombocytopenia were associated with other cytopenias (low hemoglobin, low WBC). Bleeding was found in were cause the number of platelets was less than 50×103/mm3. The most important bleeding manifestation was purpura then ecchymoses. The mean platelet volume "MPV" is useful in determining the cause of thrombocytopenia. Either due to decrease production. " Low MPV " or to increase peripheral destruction " normal or high MPV ".